IHG-1 must be localised to mitochondria to decrease Smad7 expression and amplify TGF-β1-induced fibrotic responses - Hickey, Fionnuala (My University, 2013)
TGF -β1 is a prototypic proﬁbrotic cytokine and major driver of ﬁbrosis in the kidney and other organs. Induced in high glucose-1 ( IHG-1) i s a mitochondrial protein which we have recently reported to be associated with renal disease. IHG-1 ampliﬁes responses to TGF-β1 and regulates mitochondrial biogenesis by stabilising the transcriptional co-activator peroxisome proliferator-activated receptor gamma coactivator-1-alpha. Here we report that the mitochondrial localisation of IHG-1 is pivotal in the ampliﬁcation of TGF-β1 signalling . We demonstrate that IHG-1 expression is associated with repression of the endogenous TGF-β1 inhibitor Smad7. Intriguingly, expression of a non-mitochondrial deletion mutant of IHG-1 (Δmts-IHG-1) repressed TGF-β1 ﬁbrotic signalling in renal epithelial cells. In cells expressing Δmts-IHG-1 ﬁbrotic responses including CCN2/ connective tissue growth factor, ﬁbronectin and jagged-1 expression were reduced following stimulation with TGF-β1 . Δmts-IHG-1 modulation of TGF-β1 signalling was associated with increased Smad7 protein expression. Δmts-IHG-1 modulated TGF-β1 activity by increasing Smad7 protein expression as it failed to inhibit TGF-β1 transcriptional responses when endogenous Smad7 expression was knocked down. These data indicate that mitochondria modulate TGF-β1 signal transduction and that IHG-1 is a key player in this modulation.
PUBLISHED
Keywords: IHG-1; Mitochondria; TGF-beta 1; Smad7